Verdazyl Radical Building Blocks: Synthesis, Structure, and Sonogashira Cross-Coupling Reactions - Petunin P. V. Pavel Vasilievich; Martynko E. A. Ekaterina Andreevna; Trusova M. E. Marina Evgenievna; Kazantsev M. S. Maksim Sergeevich; Rybalova T. V. Tatjyana Valerjevna; Valiev R. R. Rashid Rinatovich; Uvarov M. N. Mikhail Nikolaevich; Mostovich E. A. Evgeny Alekseevich; Postnikov P. S. Pavel Sergeevich (2018, 2018)
Title screen